Smartphone Photography as a Teledentistry Method to Evaluate Anterior Composite Restorations - Haleh Valizadeh-Haghi; Safa Valizadeh-Haghi; Nasim Naslseraji; Hamed Zandian (International Journal of Dentistry)
Objective. Today, teledentistry have gain more attention than past due to the advances in technology. The aim of this study was to compare the use of smartphone photography as a method in teledentistry with the face-to-face examination in the evaluation of anterior composite restorations. Materials and Methods. In this study, photographs of 24 composite restorations in patients attended to the clinic of Ardabil Dental School were obtained using a smartphone without any additional equipment and sent by email to 10 remote observers. As a gold standard method, these restorations were evaluated by an experienced expert in restorative dentistry a face-to-face examination. In both methods FDI criteria were used to evaluate the restorations and classified them as acceptable or not. Sensitivity, specificity, positive and negative predictive values, and diagnostic accuracy of the photographic method relative to face-to-face method were calculated. Furthermore the Mann–Whitney U test was used to statistically compare the two methods in detail. Results. The sensitivity, specificity, positive predictive value, and negative predictive value of the smartphone photography method was 69.35%, 48.72%, 87.34%, and 23.75%, respectively. A diagnostic accuracy of 65.97% was obtained. Statistically, in overall the photographic method rated the restorations as better than they were in reality (face-to-face examination) (p=0.002). Conclusions. The diagnostic accuracy of the method of evaluating anterior composite restorations by smartphone photography was moderate and the use of this method in teledentistry, although was promising, needs to be improved.